Pengaruh Penggunaan Bengkung dan Herbal Compress Ball terhadap Nyeri Punggung pada Ibu Nifas - Renny Cantika Mithawati; Kristina Maharani; Qomariyah Qomariyah (An-Najat, 2025)
Postpartum lower back pain is a common complaint among women after childbirth, often caused by changes in posture, weight distribution, and muscle strain during pregnancy and labor. The pain can significantly affect a mother's ability to perform daily activities and care for her newborn. In Indonesia, as reported by various studies, a substantial percentage of women experience persistent lower back pain postpartum, with many seeking alternative therapies to alleviate their discomfort. This study aimed to assess the effectiveness of using an abdominal binder (bengkung) and herbal compress balls in reducing postpartum lower back pain. The abdominal binder has traditionally been used to support the abdominal muscles and lower back, promoting proper posture and reducing strain on the spine. Similarly, herbal compress balls, which contain natural ingredients known for their anti-inflammatory and muscle-relaxing properties, are often applied to relieve pain and promote healing in postpartum women. The study's quasi-experimental design with a nonequivalent control group provided valuable insights into the combined impact of these two interventions. By comparing the results of the intervention group, which received both the abdominal binder and herbal compress ball, with the control group, which only received the abdominal binder, the researchers were able to identify the additional benefits of the herbal compress ball. The significant reduction in lower back pain, as indicated by the Mann-Whitney test (Z-value of -4.060, p < 0.05), suggests that the combination of these two therapies is more effective than using the abdominal binder alone. The results of this study have important implications for postpartum care. By incorporating non-pharmacological interventions such as abdominal binders and herbal compress balls, healthcare providers can offer more accessible and holistic pain relief options for new mothers, helping to enhance their comfort and recovery during the critical postpartum period.